Milkman - Burns, Anna (London Faber&Faber, 2018)
In 1970s Northern Ireland, middle sister stands out for the wrong reasons. She reads while walking, for one. And she has been taking French night classes downtown. So when a local paramilitary known as the milkman begins pursuing her, she suddenly becomes "interesting," the last thing she ever wanted to be. Despite middle sister's attempts to avoid him -- and to keep her mother from finding out about her maybe-boyfriend -- rumors spread and the threat of violence lingers. Milkman is a story of the way inaction can have enormous repercussions, in a time when the wrong flag, wrong religion, or even a sunset can be subversive.
Keywords: English fiction--Irish authors